Indonesia’s 1st livestock vessel: deep insight of it is facility - Shabrina Dyah Wibawanti; Rudi Afnan; Rudy Priyanto (Faculty of Animal Science, Universitas Brawijaya, 2021)
Indonesia is an island country consisting of thousands of islands. The population of Indo-nesian people is increasing annually, making the need for food also increases, especially food originated from the livestock sector, namely beef. The difference in consumer centers' location with cattle production centers causes the need for transportation that can transport cattle from one island to another. Camara Nusantara is the first livestock vessel in Indonesia that started in 2015. Camara Nusantara took the ship's design from Australi-an livestock vessels, but there have not been any studies on the facilities and design of the Camara Nusantara ship. This research took place in Camara Nusantara ship for 5 days from Kupang, East Nusa Tenggara to Tanjung Priuk, Jakarta. The observation was done by noting and observing all facilities used from the livestock loading process in the port of Tenau to Tanjung Priok port. The results showed that there were still many shortcomings in the facilities used, so the need for improvement is done to avoid any stress generated during the transportation process that can cause further loss.